Mechanical properties of mudstone caprock and influencing factors: implications for evaluation of caprock integrity - Jia, Ru; Fu, Xiaofei; Jin, Yejun; Wu, Tong; Wang, Sheng; Cheng, Huijie (Frontiers in Earth Science, 2023)
Mudstone is the most common cap rock in petroliferous basins. The mechanical properties of mudstone in different areas and buried depths are obviously different, which directly affects the brittleness and ductileness of caprock and its deformation characteristic. This research carried out X ray diffraction (XRD) rock mineral composition analysis, microscopic observation of mineral structural characteristics and rock mechanics triaxial compression tests under different conditions on six groups of mudstone samples from three basins. On this basis, establish numerical model to simulate the fracture deformation of mudstone under geological conditions, and to clarify the influence of different factors on the rock mechanics of mudstone. Compare and analyze the fracture characteristics and stress-strain curves of mudstone samples after the test show that, the confining pressure is the most direct factor affecting the mechanical properties and deformation mechanism of mudstone in the range of oil and gas enrichment depth. Although the formation temperature has a certain influence on the rock deformation, the effect is very limited, and it is difficult to have an essential influence on the rock deformation without the action of confining pressure. The mineral composition of mudstone is also one of the main factors affecting the mechanical deformation of rock. The comparison between the content of main minerals and the mechanical parameters of rock shows that the mechanical properties of rock and the transformation of brittleness and ductileness of mudstone have the most obvious correlation with clay minerals. Numerical simulations show that, pore fluid pressure is an important factor that cannot be ignored in overpressured caprocks. Higher pore fluid pressure can significantly inhibit the transition process of rock brittleness and ductileness, and at the same time affect the fracture mode of mudstone, which is of great significance for the evaluation of caprock integrity.